Don't Criticize Me Buddy: The Kingston Trio and the Folk Music Revival - King, Jordan (My University, 2012)
At the onset of the 1960s, the folk music revival helped to quench middle-class Americans' appetite for authenticity in the postwar world. Americans longed for a more genuine approach to life that embraced the authentic ways of an idealized culture in which life was composed not of artificial sterilities concocted by the mass media but the vital spirit of personal feeling. The folk music revival satisfied the contradictions of postwar life, but created further conflict within the world of folk music. The Kingston Trio embodied the contradictions of postwar living, making the group controversial to folk scholars and musicians. The group's professional and commercial nature divided the folk music community on the definition of authenticity. Scholars and folk musicians attempted to comprehend the correct place of the Kingston Trio in the folk music spectrum. The struggle to categorize the Kingston Trio reflected the conflict between postwar ideals and the yearning of Americans for authenticity. By merging the contradictions of postwar living, the Kingston Trio offered Americans an outlet for their desire for authenticity. The commercial nature of the group displaced the traditional folk style with a transformed folk music that better suited the needs of postwar America, making the Kingston Trio a crucial figure in American cultural history.
Keywords: Music criticism; Folk music; Musical groups; Popular culture